Reaction mechanism for the replacement of calcite by dolomite and siderite: Implications for geochemistry, microstructure and porosity evolution during hydrothermal mineralisation - Pearce, M.; Timms, Nicholas Eric; Hough, R.; Cleverley, J. (Springer, 2013)
Carbonate reactions are common in mineral deposits due to CO2-rich mineralising fluids. This study presents the first in-depth, integrated analysis of microstructure and microchemistry of fluid-mediated carbonate reaction textures at hydrothermal conditions. In doing so, we describe the mechanisms by which carbonate phases replace one another, and the implications for the evolution of geochemistry, rock microstructures and porosity. The sample from the 1.95 Moz Junction gold deposit, Western Australia, contains calcite derived from carbonation of a metamorphic amphibole—plagioclase assemblage that has further altered to siderite and dolomite. The calcite is porous and contains iron-rich calcite blebs interpreted to have resulted from fluid-mediated replacement of compositionally heterogeneous amphiboles. The siderite is polycrystalline but nucleates topotactically on the calcite. As a result, the boundaries between adjacent grains are low-angle boundaries (<10°), which are geometrically similar to those formed by crystal–plastic deformation and recovery. Growth zoning within individual siderite grains shows that the low-angle boundaries are growth features and not due to deformation. Low-angle boundaries develop due to the propagation of defects at grain faces and zone boundaries and by impingement of grains that nucleated with small misorientations relative to each other during grain growth.The cores of siderite grains are aligned with the twin planes in the parent calcite crystal showing that the reactant Fe entered the crystal along the twin boundaries. Dolomite grains, many of which appear to in-fill space generated by the siderite replacement, also show alignment of cores along the calcite twin planes, suggesting that they did not grow into space but replaced the calcite. Where dolomite is seen directly replacing calcite, it nucleates on the Fe-rich calcite due to the increased compatibility of the Fe-bearing calcite lattice relative to the pure calcite. Both reactions are interpreted as fluid-mediated replacement reactions which use the crystallography and elemental chemistry of the calcite. Experiments of fluid-mediated replacement reactions show that they proceed much faster than diffusion-based reactions. This is important when considering the rates of reactions relative to fluid flow in mineralising systems.